2020
DOI: 10.1093/schbul/sbaa030.431
|View full text |Cite
|
Sign up to set email alerts
|

M119. Deconstructing Psychosis and Cross-Validating the R-Pas Variables Targeting Its Constructs

Abstract: Background Consistent with the contemporary literature that psychosis constructs are best represented as continuous syndromes, this study aims to determine if dimensional psychosis measures outperform traditional categorical measures, thereby improving detection of symptom severity. The Rorschach Performance Assessment System (R-PAS) contains meta-analytically supported internationally normed scales for assessing disordered thinking and reality testing that have been replicated in many countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…With SevCog probably being a less severe indication of reality testing problems and risk of psychosis, unless extremely high, this coincides with our clinical impression during assessments that few of the 22 participants were at great risk of psychosis. In line with contemporary thinking of psychoses in dimensional terms and as continuous syndromes, relevant R-PAS variables may provide useful tools for assessing degrees and severity of psychotic processes ( Buckingham et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…With SevCog probably being a less severe indication of reality testing problems and risk of psychosis, unless extremely high, this coincides with our clinical impression during assessments that few of the 22 participants were at great risk of psychosis. In line with contemporary thinking of psychoses in dimensional terms and as continuous syndromes, relevant R-PAS variables may provide useful tools for assessing degrees and severity of psychotic processes ( Buckingham et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…More recently, Eblin and colleagues (2018) found a strong association between the R-PAS disordered thinking scale (WSumCog) and clinical ratings on a composite scale of disordered thought processes comprising TLC positive thought disorder items, the Scale for the Assessment of Positive Symptoms (Andreasen, 1984), and the Magical Ideation Scale (Eckblad & Chapman, 1983). In addition, Buckingham and colleagues (Buckingham et al, 2020) found a strong association between the R-PAS disordered thinking scale (WSumCog) and clinical ratings on a composite measure of the Brief Psychiatric Rating Scale (Overall & Gorham, 1988) Conceptual Disorganization scale and SCID-P (Structured Clinical Interview for DSM Disorders-Psychotic Screen; Spitzer et al, 1990) Loose Associations and Incoherence items.…”
Section: Contemporary Research Contributionsmentioning
confidence: 99%
“…Dimensionalizing Rorschach Measures of Disordered Thinking and Communication? Increasingly, categorical models have been strongly challenged (Kotov et al, 2017) with continued support for the dimensional nature of psychopathology (Clark et al, 1995). Rorschach measures of disordered thinking have historically used different strategies to denote the range of benign versus pathological scores.…”
Section: Future Directionsmentioning
confidence: 99%